THE ANALYSIS OF ENGLISH SPEAKING ACTIVITY IN STUDENTS’ TEXTBOOK ENTITLED WHEN ENGLISH RINGS A BELL USED BY SEVENTH GRADERS IN 2013 CURRICULUM (RETAIN, 2015)
Abstract One of the the goals of the educational system in indonesia is producing students who have good competence to face the global era. In this era, students not only should master the materials that given in class but also should be able to show what they know to others fluently and accurately. In this case, having good communication skills is needed espesially speaking skill. Therefore the speaking activity given should belong to the communicative activity in order to help them improve their speaking ability. This reasearch focus on speaking activity in stduents’ textbook entitled When English Rings a Bells which used by students in seventh graders in 2013 curriculum. There are two research questions those are; what kinds of speaking activities that presented in students textbook and do the speaking activities belong to the communicative activity. This reasearch use descriptive qualitative in order to get information about the contents of the textbook. The data sources that used is textbook entitled When English Rings a Bell used by seventh graders. Then, the instrument that used is observation by using field note in order to collect data from data sources. Next, when the data has been gotten, it will analyze by using the theory from Harmer (2007) about kinds of classroom speaking activities and theory from Littlewood (2004) which about the stages of activity from focus on form to focus on meaning. The result of this reasearch shows that there are seven kinds of speaking activities those are conversation practice, monolog, prepared talk, discussion, questionnaires, roleplay, and communication games. Then, based on the analysis, all the activities in the textbook belong to the communicative activity becuase there is no activity which totally focus on language form. Keywords: analysis, speaking, speaking activity, communicative activity. Abstract Salah satu tujuan dari sistem pendidikan di Indonesia adalah meghasilkan siswa siswi yang mampu menghadapi era global. Di era ini, siswa siswi tidak hanya dituntut untuk dapat menguasai materi yang diberikan dikelas tetapi juga harus mampu menunjukkan apa yang mereka ketahui kepada orang lain secara lancar dan tepat. Dalam hal ini, mempunyai kemampuan komunikasi yang baik sangatlah dibutuhkan khususnya kemampuan berbicara. Oleh karena itu, aktivitas berbicara yang diberikan kepada siswa haruslah termasuk dalam aktifitas komunikatif untuk membantu mereka meningkatkan kemampuan berbicara. Penelitian ini terfokus pada aktifitas berbicara yang disajikan dalam buku berjudul When English Rings a Bell yang digunakan oleh kelas 7 dalam pengajaran di kurikulum 2013. Terdapat dua rumusan masalah yaitu; apa saja aktifitas berbicara yang ada dalam buku When English Rings a Bell dan apakah aktivitas berbicara tersebut termasuk dalam aktifitas yang komunikatif. Model penelitian yang digunakan adalah deskriptif kualitatif untuk mendapatkan informasi mengenai isi dari buku tersebut. Sumber data yang digunakan adalah textbook berjudul When English Rings a Bell yang digunakan oleh kelas 7 dalam pengajaran di kurikulum 2013. Kemudian, instrumen yang digunakan adalah observasi dalam bentuk field note untuk mengumpulkan data dari sumber data. Selanjutnya, ketika data sudah didapat, data tersebut akan dianalysis dengan memggunakan teori dari Harmer (2007) mengenai macam-macam aktifitas berbicara dikelas dan teori dari Littlewood (2004) mengenai tingkatan aktifitas dari mulai aktifitas yang terfokus pada sususan bahasa sampai aktifitas yang terfokus pada makna dari bahasa yang dihasikan. Hasil dari penelitian tersebut menunjukkan bahwa terdapat tujuh macam aktifitas berbicara yaitu conversation practice, monolog, prepared talk, discussion, questionnaires, roleplay, and communication games. Kemudian, berdasarkan analisis, semua aktifitas berbicara yang ada di buku teks termasuk dalam aktifitas yang komunikatif karena tidak ada aktifitas berbicara dalam buku teks yang yang secara total terfokus pada susunan bahasa. Keywords: analisis, berbicaraaktifitas berbicara, aktifitas yang komunikatif.